Assessment of Nurses' Performance Regarding Physical Restraining in Intensive Care Units - Alaa Mahmoud Rabeh; Furat Hussien Mahmoud; Sabah Nazeh Mohammed Elderiny (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Physical restraint is used to prevent therapy discontinuation, patients' falls or injuries, and to protect patients from removing tubes, drains, or any other medical equipment connected to their body.Aim: The aim of this study was to assess nurses' performance regarding physical restraining in intensive care units.Design: A descriptive exploratory design was utilized in this study.Subject: A convenient subjects of all available nurses (N=60).Setting: The study was carried out at general intensive care unit in Al-sheikh Zayed general and specialized hospital, at 6 October City in Giza Governorate.Data collection tools: Three tools were used for data collection: (I) Self-administrated interview questionnaire related to physical restraining which included (a) Nurses' personal characteristics; (b) Nurses' knowledge and feedback related to physical restraining. (II) Physical restraint observational checklist. (III) Factors affecting nurses' performance regarding use of physical restraint.Results: The study showed, two-thirds (60%) of the studied nurses had a poor level of knowledge, nearly three quarters (73.3%) of the studied nurses had a poor level of practice regarding physical restraint; and there was a highly statistically positive correlation between total of physical restraints knowledge and practice among the studied nurses.Conclusion: The present study concluded that two-thirds of the studied nurses had an unsatisfactory level of general knowledge regarding physical restraint. Nearly three quarters of the studied nurses had a poor level of practice regarding physical restraint. Recommendations: In-service training programs are based on best practice guidelines for nurses working in ICU and integrating the physical restraint protocol into the plan of care to replace the traditional nursing care plan.